Effect of a Computer-Assisted General Medicine Diagnostic Consultation Service on Housestaff Diagnostic Strategy - Bankowitz, R. A.; McNeil, M. A.; Challinor, S. M.; Miller, R. A. (Methods of Information in Medicine, 1989)
Quick Medical Reference (QMR) is a microcomputer-based decision sup´port system designed to provide diagnostic assistance in the field of internal medicine. In addition to providing plausible diagnostic hypotheses based upon patient specific findings, the program highlights history, physical and laboratory items which are potentially useful in discriminating among the diagnoses under consideration. We have evaluated the impact of a computer-assisted diagnostic consultation service on the diagnostic and management strategy of a housestaff in a university internal medicine training program. Differential diagnoses were obtained before and after the use of the program, and a questionnaire was used to asses the educational value of the service and the effect of the service on the diagnosis and planned management. Over an eight week period, 31 cases were identified which met inclusion criteria. The QMR consultation added a diagnosis to the original list in 14 out of 31 cases. The consultation reordered the diagnosis in an additional 7 cases, and in 8 cases a diagnosis was ruled out by the use ofthe program. After the use of the program the housestaff reported they would obtain an additional lab test in 10 cases, change the order of planned tests. in two cases and eliminate a lab test in one case. The use of the program V)las rated as helpful educationally in 81 % of the cases, and helpful with respect to management in also 81 % of the cases.
Keywords: Medical Informatics Applications; Decision Support Systems; Computer-Assisted Diagnosis; Information Systems; Education